Alloy-induced phase transition and enhanced photovoltaic performance: the case of Cs3Bi2I9−xBrx perovskite solar cells. Issue 15 (1st April 2019) - Yu, Bin-Bin; Liao, Min; Yang, Jingxiu; Chen, Wei; Zhu, Yudong; Zhang, Xusheng; Duan, Tao; Yao, Weitang; Wei, Su-Huai; He, Zhubing
Abstract : Phase transition driven bandgap aberration of Cs3 Bi2 I9− x Br x perovskites by varying x was discovered for the first time. Abstract : Cs3 Bi2 I9 is a promising inorganic, nontoxic, and stable perovskite material for solar cell applications, but the power conversion efficiency of Cs3 Bi2 I9 -based solar cells is relatively low because its band gap is too large and indirect. Here we show that the band gap and optoelectronic properties of Cs3 Bi2 I9 can be improved by alloying Br into Cs3 Bi2 I9, despite the common expectation that the band gap of the Cs3 Bi2 I9− x Br x alloy will increase with Br concentration. By systematically growing and characterizing Cs3 Bi2 I9− x Br x perovskite materials, we discover that at x = 3 Cs3 Bi2 I6 Br3 shows the lowest bandgap of 2.03 eV, while that of Cs3 Bi2 I9 is 2.20 eV. Our photophysical characterization and density functional theory calculations show that this unusual band gap reduction and better optoelectronic properties at x ∼ 3 are mainly caused by a phase transition from the P 63 / mmc phase to the P 3̄ m phase. Moreover, we found that the composition engineering also leads to compact Cs3 Bi2 I6 Br3 films with high crystallinity and orientation, which results in a champion device with a PCE of 1.15%. This novel discovery will definitely deepen our understanding of Cs3 Bi2 I9− x Br x materials and afford more promising strategies for highly stable lead-free perovskite optoelectronic devices.